Sustainability in the Tobacco Sector? A Comparative Study of CSR Activities in Vietnam and the UK - Trinh, Ngoc Huyen (2013)
Since controversial industry sectors started to conduct corporate social responsibility (CSR) initiatives and promote themselves as socially responsible citizens, it becomes phenomenon that critical non-governmental organizations (NGOs) react to CSR communication by highlighting the shortcomings of CSR activities; especially what infringe the ethical stances. Moving beyond the moral argument and ethical-based values that portray the debates underpinning CSR concepts and ideas, this work aims at understanding CSR activities of tobacco sector in Vietnam and the UK and attempts to construct CSR motivating framework in the instrumental/economic perspectives. Using comparative method, the study found that CSR practices are significant influenced by the local institutions and primary motivated by the aim at maintaining long-term development. That is, although there are remarkable differences in CSR activities in Vietnam and the UK, the main objective for tobacco sector is to improve corporate sustainability which is attributed by retained public legitimacy, sustained competitive advantage and minimised risks and costs. The study also found evidence supporting that CSR activity in the UK is more systematic, institutionalised and more closely aligned with legislations than it in Vietnam. With some implications for businesses’ benefits are highlighted, the study further suggests that there is a need for transforming the whole market, for which tobacco companies are encouraged to engage in CSR and become healthier and greener.